The Effects of Gene Variations of GABRA2, GABRB1, GABRG2, GAD1 and SLC1A3 on Patients with Propofol During Anesthesia Induction - Zhang L; Zheng Z; Ma W; Zhang S; Xue F; Wang H; He Y; Ye F; Zhou S; Wen Y; Li X; Huang W; et al. (Dove Medical Press, 2021)
Lingyi Zhang,1,* Zhuoling Zheng,2,* Wudi Ma,1 Shuyu Zhang,3,4 Faling Xue,1 Haini Wang,5 Yongqi He,6 Fang Ye,1 Shouning Zhou,6 Yongzi Wen,3,4 Xiaoyan Li,2 Wenqi Huang,1 Min Huang,3,4 Jiali Li,3,4,* Zhongxing Wang1,* 1Department of Anesthesiology, The First Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, People's Republic of China; 2Department of Pharmacy, The Sixth Affiliated Hospital of Sun Yat-Sen University, Guangzhou, Guangdong, People's Republic of China; 3Institute of Clinical Pharmacology, School of Pharmaceutical Sciences, Sun Yat-sen University, Guangzhou, Guangdong, People's Republic of China; 4Guangdong Provincial Key Laboratory of New Drug Design and Evaluation, School of Pharmaceutical Sciences, Sun Yat-sen University, Guangzhou, Guangdong, People's Republic of China; 5Department of Pharmacy, Shenzhen Second People's Hospital, Shenzhen, Guangdong, People's Republic of China; 6Department of Pharmacy, The First Affiliated Hospital of Guangzhou Medical University, Guangzhou, Guangdong, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhongxing WangDepartment of Anesthesiology, The First Affiliated Hospital of Sun Yat-sen University, 58 Zhongshan Road 2, Guangzhou, 510080, People's Republic of ChinaTel +86-20-87755766Email wzhxing@mail.sysu.edu.cnJiali LiInstitute of Clinical Pharmacology, School of Pharmaceutical Sciences, Sun Yat-sen University, 132 Waihuan Dong Road, University City, Guangzhou, 510006, People's Republic of ChinaTel +86-20-39943034Email lijiali5@mail.sysu.edu.cnPurpose: Propofol is one of the most commonly used intravenous sedatives in general anesthesia, while the individual variations of propofol are apparent. The objective of this study was to investigate the influence of genetic variations in GABAergic neurons and glutamatergic neurons on time to loss of consciousness (LOC) and the incidence of hypotension during anesthesia induction.Patients and Methods: A total of 140 Chinese patients undergoing thyroid surgery or breast surgery were recruited. Genotyping of candidate genes was carried out using the Agena Bioscience MassARRAY system. Anesthesia induction was initiated with a propofol target plasma concentration (Cp) of 4.0 μg mL− 1. The LOC latency, systolic blood pressure, diastolic blood pressure, mean arterial pressure were documented.Results: We found that GABRA2 rs35496835, GABRB1 rs1372496, GABRG2 rs11135176, GABRG2 rs209358, GAD1 rs3791878, SLC1A3 rs1049522 and gender were significant determinants of the patient's LOC latency following propofol administration. GABRA2 rs11503014 was highly correlated with blood pressure reduction during anesthesia induction. Multiple linear regression analysis revealed that GABRB1 rs1372496, GABRG2 rs11135176, and SLC1A3 rs1049522 accounted for 35.3% variations in LOC latency following propofol administration.Conclusion: Our findings indicate that genetic variants of GABRA2, GABRB1, GABRG2, GAD1 and SLC1A3 may have influence on propofol susceptibility, which would be an important guidance towards building clinical models that can precisely predict the efficacy of propofol with various populations before surgery.Keywords: propofol, anesthesia, GABRB1, LOC latency